Pedagogical Principles Underpinning STEAM Education in Early Childhood: A Systematic Literature Review - Afrilliany, Afrilliany; Juhanaini, Juhanaini; Zaman, Badru (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2026)
STEAM education in early childhood is increasingly promoted as an integrated approach for supporting children’s creativity, inquiry, collaboration, and problem solving. However, the pedagogical principles that make STEAM developmentally appropriate remain dispersed across studies on classroom activities, media use, teacher learning, and implementation outcomes. This systematic literature review synthesized peer reviewed English language articles on STEAM or STEM learning in early childhood education published between 2015 and 2025. Searches were conducted in Scopus, ERIC, ScienceDirect, and Google Scholar via Publish or Perish using Boolean keyword combinations. Following PRISMA 2020, 327 records were identified, 79 duplicates were removed, 248 titles and abstracts were screened, 67 full texts were assessed, and 30 articles were included. The included studies were examined through quality appraisal, structured data extraction, and thematic synthesis. The synthesis identified seven interconnected pedagogical principles: child centered learning, inquiry based exploration, experiential and play based learning, interdisciplinary integration, creativity and arts integration, collaborative learning, and teacher facilitation. Child centered learning and inquiry based exploration operated as the core principles, while play, arts, collaboration, and teacher facilitation supported children’s meaning making across STEAM domains. This review contributes to the global literature on early childhood education by offering an integrated and transferable typology for understanding STEAM as a developmentally responsive pedagogical ecology rather than a collection of isolated projects. The typology can inform curriculum design, teacher professional learning, assessment practices, and future classroom based research across diverse early childhood contexts.